Beverage intake during alternate-day fasting: Relationship to energy intake and body weight. Issue 3 (September 2019) - Kalam, Faiza; Kroeger, Cynthia M; Trepanowski, John F; Gabel, Kelsey; Song, Jee Hee; Cienfuegos, Sofia; Varady, Krista A
Background: Alternate-day fasting (ADF) involves a 'famine day' (25% energy intake) and a 'feast day' (ad libitum intake). This secondary analysis examined changes in beverage intake in relation to energy intake and body weight during 12 months of ADF versus daily calorie restriction (CR). Methods: Obese subjects ( n = 100 enrolled, n = 69 completers) were randomized to one of three groups for 12 months: (a) ADF; (b) CR; or (c) control. Results: At baseline, intakes of diet soda, caffeinated beverages, sugar-sweetened soda, alcohol, juice, and milk were similar between groups. There were no statistically significant changes in the intake of these beverages by month 6 or 12 between ADF (feast or famine day), CR, or control groups. Beverage intake was not related to energy intake or body weight at month 6 or 12 in any group. Conclusion: These pilot findings suggest that intermittent fasting does not impact beverage intake in a way that affects energy intake or body weight.